2016
DOI: 10.1071/an14571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for calving difficulty using complex genetic models in five beef breeds in Australia

Abstract: Data on Angus (ANG), Charolais (CHA), Hereford (HER), Limousin (LIM) and Simmental (SIM) cattle were used to estimate genetic parameters for calving difficulty (CD), birthweight (BWT) and gestation length (GL) using threshold-linear models and to examine the effect of inclusion of random effect of sire × herd interaction (SxH) in the models. For models without SxH, estimated heritabilities for direct genetic effect of CD were 0.24 (±0.02), 0.22 (±0.04), 0.31 (±0.02), 0.22 (±0.04) and 0.17 (±0.01) for ANG, CHA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
5
5
1
Order By: Relevance
“…The genetic correlation between birthweight and gestation length was negative, indicating that selecting for shorter gestation is likely to result in increased birthweight, in the absence of selection pressure on other traits. This negative correlation conflicts with previous reports for both dairy-breed and beef-breed cattle, (genetic correlations range 0.15-0.63 [7][8][9][10][11][12][13]), and indicates further investigation using a larger population with known maternal pedigree, and the inclusion of purebreds as well as crossbreds, would be worthwhile. In contrast, the moderate positive phenotypic correlation between birth weight and gestation length, is consistent with other studies which report a positive correlation [8,10,13,35].…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…The genetic correlation between birthweight and gestation length was negative, indicating that selecting for shorter gestation is likely to result in increased birthweight, in the absence of selection pressure on other traits. This negative correlation conflicts with previous reports for both dairy-breed and beef-breed cattle, (genetic correlations range 0.15-0.63 [7][8][9][10][11][12][13]), and indicates further investigation using a larger population with known maternal pedigree, and the inclusion of purebreds as well as crossbreds, would be worthwhile. In contrast, the moderate positive phenotypic correlation between birth weight and gestation length, is consistent with other studies which report a positive correlation [8,10,13,35].…”
Section: Discussioncontrasting
confidence: 93%
“…The variation among the sires for progeny birth weight indicated that choice of sire could change birth weight by as much as 8 kg in spring-calving herds, even when selecting sires from within the same breed. The lighter calves from Angus bulls than from the Hereford bulls used in this case study was consistent with previous literature that reported a 1.4-3.5 kg greater birth weight for Hereford than Angus calves [12,[19][20][21][22]. It should be highlighted that the current study was not a breed comparison, because individual bulls were selected to achieve a spread of EBV and were not a random sample from the breed, and, therefore, may not accurately represent the breed as a whole.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The negative genetic correlations between direct and maternal genetic effects observed in the current study is consistent with several others (Cervantes et al, 2010;Jeyaruban et al, 2015;Johanson et al, 2011) and could be a mechanism to keep GL of cows within a narrow range (i.e., SD). Consequently, it is common for genetic correlations between direct and maternal effects to be negative (McClintock, 2004;Johanson et al, 2011).…”
Section: Discussionsupporting
confidence: 91%